2018
DOI: 10.5144/0256-4947.2018.481
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in mortality among ST elevation myocardial infarction patients in Malaysia from 2006 to 2013

Abstract: BACKGROUND: Coronary artery disease (CAD) is one of the leading causes of death in Malaysia. However, the prevalence of CAD in males is higher than in females and mortality rates are also different between the two genders. This suggest that risk factors associated with mortality between males and females are different, so we compared the clinical characteristics and outcome between male and female STEMI patients. OBJECTIVES: To identify the risk factors associated with mortality for each gender and compare dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Hence, the gender of patients itself does not determine the prognosis of the patient, but longer ischemic time, older age, and consequently higher burden of risk factors confound the effect of the female gender as observed by various studies in the past. [5][6][7][8][9]23 One of the major determinants of adverse outcomes in patients with STEMI is the pre-hospital delays. The timeline in the management of STEMI is different in females compared to their male counterparts, females experience longer gaps not only in symptoms to hospital arrival but also from hospital arrival to the procedure time, causing a delay in the reinstatement of myocardium on time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the gender of patients itself does not determine the prognosis of the patient, but longer ischemic time, older age, and consequently higher burden of risk factors confound the effect of the female gender as observed by various studies in the past. [5][6][7][8][9]23 One of the major determinants of adverse outcomes in patients with STEMI is the pre-hospital delays. The timeline in the management of STEMI is different in females compared to their male counterparts, females experience longer gaps not only in symptoms to hospital arrival but also from hospital arrival to the procedure time, causing a delay in the reinstatement of myocardium on time.…”
Section: Discussionmentioning
confidence: 99%
“…Different researches have been conducted that show female gender is linked to the increased risks of immediate and longterm death following cardiovascular events. [4][5][6][7][8][9][10][11] However, there is a contradiction of evidence because there are plenty of studies showing no variances in results or attributed differences in outcomes to the variations in baseline features such as a higher burden of comorbidities in females owing to advanced age at the time of presentation. 12,13 Multiple factors associated with an increased rate of severe events in females have been depicted by studies centering on outcomes of gender disparities, such as some studies have shown that females are more likely to have the atypical medical presentation and prehospital delays than males leading to delay in reperfusion therapy.…”
Section: Introductionmentioning
confidence: 99%